Sosialisasi Pencegahan Peredaran BBM Oplosan di Masyarakat - Jusuf Leiwakabessy; Esterlina E. E. M. Nanlohy; Sherly Lewerissa; Evan R. Ferdinandus (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The increase in oil prices and other living expenses has contributed to the rise of illegal fuel adulteration practices. In order to make huge profits from the minimal cost of fuel production and distribution, certain individuals are willing to carry out these illegal practices, despite the risks and impacts they cause. The lack of knowledge and awareness in communities about adulterated fuels, as well as the lack of encouragement from the government to eradicate them, has also increased the number of these illegal practices. Being a progressive village with numerous people and activities, Passo Village needs a proper sustainable fuel supply. Therefore, it is important to raise awareness in Passo Village’s community about the characteristics and dangers of adulterated fuels in order to prevent their circulation and the practices involved. On account of this objective, the socialization program has been conducted in Passo Village in the method of material presentation.